Preparation method of fine-grain alumina ceramic
Through powder pretreatment and sol treatment, combined with the second phase additive and casting technology, the agglomeration and dispersion of nano-alumina powders during molding and sintering are solved, and the high performance of fine crystalline alumina ceramics is achieved Preparation improves the density and electrical properties of the ceramic.
Patent Information
- Application Number
- CN202411044207.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-13
AI Technical Summary
Nano-scale alumina powder is prone to agglomeration and dispersion during molding and sintering, resulting in green defects and abnormal growth of grains, affecting the density, mechanical strength and electrical properties of the ceramic.
Using powder pretreatment, sol treatment and two-step sintering technology, the dispersion and ball milling of nano alumina powders are carried out through horizontal ball milling, planetary ball milling and drum ball milling. The second phase additives such as Y2O3 and MgO are added, and PEG is combined with and PVB colloids, casting and vacuum or hot press sintering, control the sintering temperature and pressure to obtain a fine crystal structure.
It effectively reduces the defects of the blank, prevents the abnormal growth of alumina grains, improves the density and comprehensive performance of the ceramics, and obtains excellent mechanical properties and electrical properties.
Smart Images

Figure CN119118633A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrostatic chucks, and in particular to a method for preparing fine-grained alumina ceramics. Background Art
[0002] Among the existing solutions, high-purity, high-performance alumina ceramics have been widely used in the semiconductor industry. Compared with non-oxide ceramics such as aluminum nitride and silicon carbide, their fracture toughness, fracture strength, hardness, thermal shock resistance, wear resistance and electrical properties are insufficient, which limits their application in the field of electrostatic chucks. The development of high-performance fine-grained alumina ceramics gives alumina ceramics the following advantages:
[0003] (1) Better mechanical properties: The fine grain structure can significantly improve the strength and toughness of the material, which makes high-performance fine-grained alumina ceramics better in terms of fracture resistance and impact resistance;
[0004] (2) Higher hardness and wear resistance: The fine grain structure can reduce the roughness of the material surface, thereby improving its hardness and wear resistance, making it suitable for high wear environments;
[0005] (3) Higher thermal stability and thermal conductivity: The fine grain structure helps to improve the thermal conductivity and thermal stability of the material, enabling it to maintain excellent performance in high temperature environments;
[0006] (4) Excellent electrical properties: Fine-grained alumina ceramics have better insulation properties and dielectric strength, and are suitable for use in electronic and electrical insulation materials, which helps to improve the dielectric properties and compressive strength of the dielectric layer of the electrostatic chuck.
[0007] The main purpose of fine-grained alumina ceramics is to improve the comprehensive performance of the material by optimizing its microstructure. The internal stress of the grain boundary material in the fine-grained structure is reduced, which is not easy to cause transgranular fracture, can effectively prevent the expansion of cracks, and improve the strength and toughness of the material. In addition, fine grains can also improve the density and uniformity of the material, thereby improving its mechanical and electrical properties. In addition, fine-grained alumina ceramics use nano-scale alumina powder, which has high sintering activity and can greatly reduce the sintering temperature, which is conducive to cost savings. However, nano-scale alumina powder is easy to agglomerate and difficult to disperse, which will cause defects in the molding process; secondly, fine materials have higher surface activity, and chemical reactions are easy to occur during the sintering process, causing abnormal grain growth. How to regulate the structure of fine-grained alumina from both molding and sintering has always been a technical difficulty in this field.
[0008] The method of adding sintering aids is to reduce the sintering temperature or pin on the grain boundary in the form of a second phase to reduce the grain boundary migration rate and increase the grain boundary diffusion to achieve the nano-sizing of ceramics. In semiconductor precision ceramics, the grain size of ceramics is one of the important factors affecting its mechanical properties, electrical properties and thermal properties. Usually, the morphology, particle size, particle size distribution, BET and purity of nano-alumina powder determine the performance of alumina ceramics. Ceramic chucks prepared from powders with low sodium and iron content have better pressure resistance. In addition to particle size distribution, a decisive factor affecting the grain size of alumina ceramics is the sintering system. Generally, special sintering technologies such as low-temperature sintering or two-step sintering, discharge plasma sintering, and oscillation pressure sintering are used to inhibit the growth of alumina grains, thereby obtaining a fine-grained structure. The method of adding sintering aids to fine-grained alumina ceramics is to reduce the sintering temperature or pin on the grain boundary in the form of a second phase to reduce the grain boundary migration rate and increase the grain boundary diffusion to achieve the nano-sizing of ceramics.
[0009] The ceramic dielectric layer of the electrostatic chuck has high requirements on the density of the ceramic. According to the empirical formula The sintering density of ceramic materials is achieved at the expense of grain size, so the control of the sintering process is crucial. Chu and Chen reported the preparation of nanoceramics by two different methods. The former can regulate the microstructure of ceramics, but the prepared grain size is larger. The latter uses the first step of high temperature T1 to make the ceramic reach a certain density, and then quickly cools down and keeps it at a lower temperature T2 for a long time to achieve complete densification. The grain size can be controlled between 500 and 1μm. The selection of T1 and T2 temperatures is mainly to regulate the degree of grain boundary migration and grain boundary diffusion, inhibit grain boundary migration, and thus control the grain size. In addition, adding second phase hard particles to inhibit the migration of alumina grain boundaries is also an effective means to obtain fine-grained alumina ceramics. Other sintering techniques such as hot pressing sintering, SPS sintering, and hot isostatic pressing sintering can inhibit grain growth, but the balance control of grain size and densification process, and the influence of additives on the overall performance of ceramics are also very important.
[0010] Problems with existing technologies:
[0011] In terms of molding:
[0012] (1) Nano-alumina powder is easy to agglomerate and difficult to disperse, which will cause green defects during the molding process;
[0013] (2) Nanopowders have a large specific surface area, which can easily lead to stratification during lamination or subsequent debinding and sintering processes.
[0014] In terms of sintering: fine powder has high surface activity, and chemical reactions are likely to occur during the sintering process, causing abnormal grain growth. If the shrinkage in the transverse and thickness directions is different during the sintering process, cracking and deformation are likely to occur. When preparing fine-grained alumina ceramics, it is difficult to achieve both sintering density and appropriate grain size, which affects the density, mechanical strength and electrical properties of the product. Summary of the invention
[0015] The technical problem to be solved by the present invention is to provide a method for preparing fine-grained alumina ceramics to solve the problems raised in the background technology.
[0016] In order to solve the above technical problems, the technical solution of the present invention is:
[0017] A method for preparing fine-grained alumina ceramics, the preparation method comprising:
[0018] Powder pretreatment: disperse the nano-alumina powder in a horizontal ball mill, the ball milling beads are of two types, 1 mm in diameter and 0.5 mm in diameter, the ratio of the two ball milling beads is 1:2, the ball milling time is 3 to 6 hours, the rotation speed is 500 to 1000 RPM, and the volume ratio of the grinding medium to the material is 3:1; add the second phase additive, the second phase additive is any one of Y2O3, CeO2, MgO, nano-SiC spherical particles, silicon nitride, ZrO2, and a mixture of two or more, the purity of the second phase additive is greater than or equal to 99.99%, and the volume fraction of the second phase additive accounts for 1 to 10% of the total, first mix the second phase additive with the solvent, then add the structure directing agent PEG and the dispersant, ball mill at 400 RPM for 2 hours in the planetary ball mill, and finally transfer the resulting solution to a vertical stirred mill for grinding;
[0019] Sol: first add 60 parts of toluene, 20 parts of isopropanol and 20 parts of plasticizer into a pneumatic sol machine, slowly and evenly stir for 10 minutes, then slowly add 30-50 parts of adhesive in small amounts several times, stir at high speed for 3 hours to ensure that the adhesive is evenly and fully dissolved, age for 6 hours, filter with a 2μm filter and set aside;
[0020] Dispersion: First weigh a certain amount of 3mm balls, toluene and n-butanol mixed solvent in a stirred mill, the ratio of toluene to n-butanol is 3:1-2:1, then add the pretreated second phase additive, nano alumina powder dispersant and additives in sequence, turn on the stirring switch and stir for 2 hours, the ratio of alumina is 90%-99%;
[0021] Mixing: transfer the alumina and second phase additive slurry in the stirred mill to the drum ball mill, add a certain amount of PVB colloid according to the formula, run at a certain stirring rate for 24 hours, and transfer to the degassing tank through a 1μm filter;
[0022] Vacuum degassing: After the slurry in the drum ball mill is sent into the degassing tank with N2 gas pressure, the viscosity of the slurry and the corresponding ambient temperature are measured, and the water bath temperature is set according to the slurry viscosity and temperature, and the appropriate degassing vacuum degree and time are set. After the slurry is effectively degassed, it is aged for a period of time for use;
[0023] Molding and sintering: Set the scraper blade height to 0.3-0.6mm, the casting speed to 1-300mm / min, set the temperature and inlet and outlet air flux according to the environment, and adjust the casting speed and heating temperature appropriately according to the shrinkage of the drying area, so that the solvent volatilization on the surface and the back will not differ too much. The casting temperature and environment should also be strictly controlled to prevent the green body from delamination during the lamination process;
[0024] After cutting, punching, printing, lamination and warm isostatic pressing for secondary molding, a block green body is obtained, and finally the binder is removed and sintered. The two-step sintering method is adopted. The sintering is vacuum sintering, hot pressing sintering under argon protective atmosphere or isostatic pressing sintering. The sintering temperature is 1500-1850°C, the sintering pressure is 20-50Mpa, and the temperature is kept for 1 hour, slowly cooled to 1500°C, kept for 2 hours, and then naturally cooled to room temperature to obtain high-performance nano-alumina ceramics.
[0025] Preferably, the nano-alumina powder is nano-high-purity alumina powder, γ or α phase spherical particles, purity greater than or equal to 99.99%, particle size D50 = 200nm, D10 and D90 ratio of 1:2 to 1:3, BET = 5 to 14m 2 / g.
[0026] Preferably, the second phase additives are Y2O3 and MgO, wherein the particle sizes of Y2O3 and MgO are 100nm-300nm, D10=30-50nm, D90=250-300nm, D90 / D10=4, and the ratio of Y2O3 to MgO is 1:2.
[0027] Preferably, the solvent is any one of toluene, xylene, N-methylpyrrolidone, anhydrous ethanol, isopropanol, n-butanol, or a mixture of two or more thereof, with a purity greater than or equal to 99.99% and a water content less than or equal to 0.05%.
[0028] Preferably, the adhesive is PVB resin powder or polymethacrylic acid resin with a molecular weight of 30,000 to 130,000.
[0029] Preferably, the plasticizer is dibutyl phthalate.
[0030] Preferably, the dispersant is any one of KD-1, fish oil, lecithin, oleic acid amide, and a surfactant.
[0031] The above technical solution has the following beneficial effects:
[0032] The present application discloses a method for preparing fine-grained nano-alumina ceramics by tape casting and sintering. The pre-dispersion process effectively reduces the defects of the green body. The structure-directing agent PEG makes the second phase additives such as MgO and Y2O3 evenly distributed in the matrix to prevent the abnormal growth of the alumina grains. The two-step sintering method effectively inhibits the growth of the grains. The pinning effect and liquid phase sintering mechanism of the second phase additives such as MgO and Y2O3 refine the grain size of the alumina ceramics and increase the density of the ceramics, thereby obtaining excellent mechanical and electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of the microstructure of Al2O3 ceramics prepared in the present invention. DETAILED DESCRIPTION
[0034] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0035] Example 1
[0036] A method for preparing fine-grained alumina ceramics, comprising:
[0037] Powder pretreatment: disperse the nano-alumina powder in a horizontal ball mill. The ball milling beads are of two types, 1 mm in diameter and 0.5 mm in diameter. The ratio of the two ball milling beads is 1:2. The ball milling time is 3 to 6 hours. The rotation speed is 500 to 1000 RPM. The volume ratio of the grinding medium to the material is 3:1. Add the second phase additive, which is any one of Y2O3, CeO2, MgO, nano-SiC spherical particles, silicon nitride, and ZrO2, or a mixture of two or more. The purity of the second phase additive is greater than or equal to 99.99%, the volume fraction of the second phase additive accounts for 1-10% of the total, the second phase additive is first mixed with a solvent, and then a structure directing agent PEG and a dispersant are added, and the mixture is ball-milled at 400RPM for 2h in a planetary ball mill, and finally the resulting solution is transferred to a vertical stirred mill for grinding, wherein the solvent is any one of toluene, xylene, N-methylpyrrolidone, anhydrous ethanol, isopropanol, and n-butanol, and a mixture of two or more thereof, with a purity greater than or equal to 99.99%, and a water content less than or equal to 0.05%;
[0038] Sol: first add 60 parts of toluene, 20 parts of isopropanol and 20 parts of plasticizer into a pneumatic sol machine, slowly and evenly stir for 10 minutes, then slowly add 30-50 parts of adhesive in small amounts several times, stir at high speed for 3 hours to ensure that the adhesive is evenly and fully dissolved, age for 6 hours, filter with a 2μm filter and set aside;
[0039] Dispersion: First weigh a certain amount of 3mm balls, toluene and n-butanol mixed solvent in a stirred mill, the ratio of toluene to n-butanol is 3:1-2:1, then add the pretreated second phase additive, nano alumina powder dispersant and additives in sequence, turn on the stirring switch and stir for 2 hours, the ratio of alumina is 90%-99%;
[0040] Mixing: transfer the alumina and second phase additive slurry in the stirred mill to the drum ball mill, add a certain amount of PVB colloid according to the formula, run at a certain stirring rate for 24 hours, and transfer to the degassing tank through a 1μm filter;
[0041] Vacuum degassing: After the slurry in the drum ball mill is sent into the degassing tank with N2 gas pressure, the viscosity of the slurry and the corresponding ambient temperature are measured, and the water bath temperature is set according to the slurry viscosity and temperature, and the appropriate degassing vacuum degree and time are set. After the slurry is effectively degassed, it is aged for a period of time for use;
[0042] Molding and sintering: Set the scraper blade height to 0.3-0.6mm, the casting speed to 1-300mm / min, set the temperature and inlet and outlet air flux according to the environment, and adjust the casting speed and heating temperature appropriately according to the shrinkage of the drying area, so that the solvent volatilization on the surface and the back will not differ too much. The casting temperature and environment should also be strictly controlled to prevent the green body from delamination during the lamination process;
[0043] After cutting, punching, printing, lamination and warm isostatic pressing for secondary molding, a block green body is obtained, and finally the binder is removed and sintered. The two-step sintering method is adopted. The sintering is vacuum sintering, hot pressing sintering under argon protective atmosphere or isostatic pressing sintering. The sintering temperature is 1500-1850°C, the sintering pressure is 20-50Mpa, and the temperature is kept for 1 hour, slowly cooled to 1500°C, kept for 2 hours, and then naturally cooled to room temperature to obtain high-performance nano-alumina ceramics.
[0044] Example 2
[0045] A method for preparing fine-grained alumina ceramics, comprising:
[0046] Powder pretreatment: Nano-alumina powder is dispersed in a horizontal ball mill. The ball milling beads are of two types, 1 mm in diameter and 0.5 mm in diameter. The ratio of the two ball milling beads is 1:2. The ball milling time is 3 hours. The rotation speed is 50 RPM. The volume ratio of the grinding medium to the material is 3:1. The second phase additive is added. The second phase additive is any one of Y2O3, CeO2, MgO, nano-SiC spherical particles, silicon nitride, ZrO2, or a mixture of two or more. The purity of the second phase additive is greater than or equal to 99. 99%, the volume fraction of the second phase additive accounts for 1% of the total, the second phase additive is first mixed with the solvent, and then the structure directing agent PEG and the dispersant are added, and the ball milling is carried out at 400RPM for 2h in a planetary ball mill, and finally the obtained solution is transferred to a vertical stirred mill for grinding, wherein the solvent is any one of toluene, xylene, N-methylpyrrolidone, anhydrous ethanol, isopropanol, and n-butanol, and a mixture of two or more thereof, with a purity greater than or equal to 99.99%, and a water content less than or equal to 0.05%;
[0047] Sol: first add 60 parts of toluene, 20 parts of isopropanol and 20 parts of plasticizer into a pneumatic sol machine, slowly and evenly stir for 10 minutes, then slowly add 30 parts of adhesive in small amounts several times, stir at high speed for 3 hours to ensure that the adhesive is evenly and fully dissolved, age for 6 hours, filter with a 2μm filter and set aside;
[0048] Dispersion: First weigh a certain amount of 3mm balls, toluene and n-butanol mixed solvent into a stirred mill, the ratio of toluene to n-butanol is 3:1-2:1, then add the pretreated second phase additive, nano alumina powder dispersant and additives in sequence, turn on the stirring switch and stir for 2 hours, the ratio of alumina is 90%;
[0049] Mixing: transfer the alumina and second phase additive slurry in the stirred mill to the drum ball mill, add a certain amount of PVB colloid according to the formula, run at a certain stirring rate for 24 hours, and transfer to the degassing tank through a 1μm filter;
[0050] Vacuum degassing: After the slurry in the drum ball mill is sent into the degassing tank with N2 gas pressure, the viscosity of the slurry and the corresponding ambient temperature are measured, and the water bath temperature is set according to the slurry viscosity and temperature, and the appropriate degassing vacuum degree and time are set. After the slurry is effectively degassed, it is aged for a period of time for use;
[0051] Molding and sintering: Set the scraper blade height to 0.3mm, the casting speed to 1mm / min, set the temperature and inlet and outlet air flux according to the environment, and adjust the casting speed and heating temperature appropriately according to the shrinkage of the drying area, so that the solvent volatilization on the surface and the back will not differ too much. The casting temperature and environment should also be strictly controlled to prevent the green body from delamination during the lamination process;
[0052] After cutting, punching, printing, lamination and warm isostatic pressing for secondary molding, a block green body is obtained, and finally the binder is removed and sintered. The sintering is carried out in two steps. The sintering is vacuum sintering, hot pressing sintering under argon protective atmosphere or isostatic pressing sintering. The sintering temperature is 1500°C, the sintering pressure is 20Mpa, and the temperature is kept for 1 hour. Then, the temperature of 1500°C is kept for 2 hours, and then naturally cooled to room temperature to obtain high-performance nano-alumina ceramics.
[0053] Example 3
[0054] A method for preparing fine-grained alumina ceramics, comprising:
[0055] Powder pretreatment: disperse the nano-alumina powder in a horizontal ball mill. The ball milling beads are of two types, 1 mm in diameter and 0.5 mm in diameter. The ratio of the two ball milling beads is 1:2. The ball milling time is 6 hours. The rotation speed is 1000 RPM. The volume ratio of the grinding medium to the material is 3:1. Add the second phase additive, which is any one of Y2O3, CeO2, MgO, nano-SiC spherical particles, silicon nitride, ZrO2, or a mixture of two or more. The purity of the second phase additive is greater than or equal to 99. .99%, the volume fraction of the second phase additive accounts for 10% of the total, the second phase additive is first mixed with the solvent, and then the structure directing agent PEG and the dispersant are added, and the ball milling is carried out at 400RPM for 2h in a planetary ball mill, and finally the obtained solution is transferred to a vertical stirred mill for grinding, wherein the solvent is any one of toluene, xylene, N-methylpyrrolidone, anhydrous ethanol, isopropanol, and n-butanol, and a mixture of two or more thereof, with a purity greater than or equal to 99.99%, and a water content less than or equal to 0.05%;
[0056] Sol: first add 60 parts of toluene, 20 parts of isopropanol and 20 parts of plasticizer into a pneumatic sol machine, slowly and evenly stir for 10 minutes, then slowly add 50 parts of adhesive in small amounts several times, stir at high speed for 3 hours to ensure that the adhesive is evenly and fully dissolved, age for 6 hours, filter with a 2μm filter and set aside;
[0057] Dispersion: First weigh a certain amount of 3mm balls, toluene and n-butanol mixed solvent in a stirred mill, the ratio of toluene to n-butanol is 3:1-2:1, then add the pretreated second phase additive, nano alumina powder dispersant and additives in sequence, turn on the stirring switch and stir for 2 hours, the ratio of alumina is 99%;
[0058] Mixing: transfer the alumina and second phase additive slurry in the stirred mill to the drum ball mill, add a certain amount of PVB colloid according to the formula, run at a certain stirring rate for 24 hours, and transfer to the degassing tank through a 1μm filter;
[0059] Vacuum degassing: After the slurry in the drum ball mill is sent into the degassing tank with N2 gas pressure, the viscosity of the slurry and the corresponding ambient temperature are measured, and the water bath temperature is set according to the slurry viscosity and temperature, and the appropriate degassing vacuum degree and time are set. After the slurry is effectively degassed, it is aged for a period of time for use;
[0060] Molding and sintering: Set the scraper blade height to 0.6mm, the casting speed to 300mm / min, set the temperature and inlet and outlet air flux according to the environment, and adjust the casting speed and heating temperature appropriately according to the shrinkage of the drying area, so that the solvent volatilization on the surface and the back will not differ too much. The casting temperature and environment should also be strictly controlled to prevent the green body from delamination during the lamination process;
[0061] After cutting, punching, printing, lamination and warm isostatic pressing for secondary molding, a block green body is obtained, and finally the binder is removed and sintered. The two-step sintering method is adopted. The sintering is vacuum sintering, hot pressing sintering under argon protective atmosphere or isostatic pressing sintering. The sintering temperature is 1500-1850℃, the sintering pressure is 50Mpa, and the temperature is kept for 1 hour, and then the temperature is slowly reduced to 1500℃, kept for 2 hours, and then naturally cooled to room temperature to obtain high-performance nano-alumina ceramics.
[0062] Example 4
[0063] A method for preparing fine-grained alumina ceramics, comprising:
[0064] Powder pretreatment: disperse the nano-alumina powder in a horizontal ball mill, preferably Nikkato's 1mm and 0.5mm diameter ball mill beads, the ratio of the two is 1:2, the ball milling time is 3-6h, the rotation speed is 500-1000RPM, the volume ratio of the grinding medium to the material is 3:1, the second phase additives are Y2O3 and MgO, wherein Y2O3 is 200nm spherical particles, MgO is 100nm spherical particles, D10=30-50nm, D90=250-300nm, D90 / D10=4, the ratio of Y2O3 is 3wt%, first dissolve Y2O3:MgO=1:2 in a mixed solvent of n-butanol and toluene, then add the structure directing agent PEG and the dispersant KD-1, ball mill at 400RPM for 2h in a planetary ball mill, and finally transfer the resulting solution to a vertical stirred mill;
[0065] Sol: PVB is preferably used as the adhesive of the casting system. First, add 60 parts of toluene, 20 parts of isopropanol and 20 parts of plasticizer into a pneumatic sol machine, stir slowly and evenly for 10 minutes, then add 30-50 parts of PVB resin powder in small amounts several times, stir at high speed for 3 hours to ensure that the adhesive is evenly and fully dissolved, and age for 6 hours, filter with a 2μm filter and set aside;
[0066] Dispersion: First weigh a certain amount of 3mm balls, toluene and n-butanol mixed solvent into a stirred mill, the ratio of toluene to n-butanol is 2:1, then add the pretreated Y2O3, MgO and nano-alumina powder dispersant and additives in sequence, turn on the stirring switch and stir for 2 hours, the proportion of alumina is 91%;
[0067] Mixing: transfer the alumina, Y2O3 and MgO slurries in the stirred mill to the drum ball mill, add a certain amount of PVB colloid according to the formula, run at a certain stirring rate for 24 hours, and transfer to the degassing tank through a 1μm filter;
[0068] Vacuum degassing: After the slurry in the drum ball mill is sent into the degassing tank with N2 gas pressure, the viscosity of the slurry and the corresponding ambient temperature are measured, and the water bath temperature is set according to the slurry viscosity and temperature, and the appropriate degassing vacuum degree and time are set. After the slurry is effectively degassed, it is aged for a period of time for use;
[0069] Molding and sintering: set the scraper blade height to 0.3-0.6mm, preferably 0.4mm, the casting speed to 200mm / min, set the temperature and inlet and outlet air flux according to the environment, and set the temperatures of Zone 1, Zone 2, Zone 3, and Zone 4 to 45°C, 48°C, 53°C, and 73°C respectively. According to the shrinkage of the drying zone, appropriately adjust the casting speed and the heating temperature of Zone 1, Zone 2, Zone 3, and Zone 4, so that the solvent volatilization on the surface and the back will not differ too much. The casting temperature and environmental moderation should also be strictly controlled to prevent the green body from being delaminated during the lamination process;
[0070] After cutting, punching, printing, lamination and warm isostatic pressing for secondary molding, a block green body is obtained, and finally the binder is removed and sintered. The two-step sintering method includes vacuum sintering, hot pressing sintering under argon protective atmosphere or isostatic pressing sintering. The sintering temperature is 1500-1850°C, kept for 1 hour, slowly cooled to 1500°C, kept for 2 hours, and then naturally cooled to room temperature to obtain high-performance nano-alumina ceramics.
[0071] Since it is difficult to densify composite materials, pressure-assisted technology is usually required, such as hot pressing (HP) or glass encapsulation hot isostatic pressing (HIP). Hot pressing sintering is preferred, with a sintering temperature of 1500°C to 1850°C, a sintering pressure of 20 to 50 MPa, and a pressure holding period of 1 to 2 hours. After pre-sintering, Na and Fe at the hot melting point can also volatilize and the green body has a certain strength, but its density is still lower than the theoretical density and the porosity is relatively high. Hot pressing sintering is performed after vacuum pre-sintering at a pressure of 30 MPa and 1800°C, which can significantly increase the density of the material and reduce the porosity, thereby greatly improving the density and obtaining excellent mechanical properties. High temperature and pressure are conducive to the growth and phase change of grains, making the microstructure of the material more perfect and further improving the performance. After applying pressure, the sintering temperature can be reduced, the migration of grain boundaries can be inhibited, and the grains can be refined.
[0072] refer to Figure 1 After adding the second phase additive, there are three distribution diagrams of the second phase additive in the main crystal phase, including intracrystalline, intercrystalline and a mixture of the two, which depends on the amount of the second phase additive and the size of the powder particle size;
[0073] The experimental process found that at the same temperature, as the volume fraction of the second phase MgO and Y2O3 in the material increased from 0% to 10%, the density first increased and then decreased. It is possible that the larger volume fraction of MgO made the liquid phase too viscous, inhibiting liquid sintering. At the same time, it can be predicted that the reaction of MgO with alumina to form magnesia-alumina spinel inclusions will have a significant hindering effect on grain growth, which will lead to the formation of a special microstructure. Y2O3 can form a low-melting-point liquid phase with alumina at high temperature, promote bonding and densification between particles, and improve sintering efficiency. The volume density of the sintered ceramic first increased and then remained unchanged with the amount of Y2O3. Y2O3 is distributed at the intersection of grain boundaries and triple points. The impact of the addition of Y2O3 is:
[0074] (a) It helps to improve the fracture toughness of alumina ceramics and reduce the risk of brittle fracture;
[0075] (b) Y2O3 can improve the insulation properties of alumina ceramics, making them perform better in high voltage environments;
[0076] (c) Y2O3 can refine the grains and distribute them evenly, improving the comprehensive performance of ceramic materials. When the pressure is 25Mpa, as the temperature increases from 1500℃ to 1800℃, the ceramic grain size is 300-600nm, the density of the composite material reaches 3.93, the maximum bending strength can reach 800Mpa, the Vickers hardness reaches 25Gpa, and the compressive strength is >35kV / mm.
[0077] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.
Claims
1. A method for preparing fine-grained alumina ceramics, It is characterized in that The preparation method comprises: Powder pretreatment: Nano-alumina powder is dispersed in a horizontal ball mill. The ball milling beads are of two types, 1 mm in diameter and 0.5 mm in diameter. The ratio of the two ball milling beads is 1:
2. The ball milling time is 3 to 6 hours. The rotation speed is 500 to 1000 RPM. The volume ratio of the grinding medium to the material is 3:
1. The second phase additive is added. The second phase additive is Y 2 O 3 、CeO 2 , MgO, nano-SiC spherical particles, silicon nitride, ZrO 2 any one of the above and a mixture of two or more of the above, the purity of the second phase additive is greater than or equal to 99.99%, the volume fraction of the second phase additive accounts for 1-10% of the total, the second phase additive is first mixed with the solvent, and then the structure directing agent PEG and the dispersant are added, and the mixture is ball-milled at 400 RPM for 2 hours in a planetary ball mill, and finally the resulting solution is transferred to a vertical stirred mill for grinding; Sol: first add 60 parts of toluene, 20 parts of isopropanol and 20 parts of plasticizer into a pneumatic sol machine, slowly and evenly stir for 10 minutes, then slowly add 30-50 parts of adhesive in small amounts several times, stir at high speed for 3 hours to ensure that the adhesive is evenly and fully dissolved, age for 6 hours, filter with a 2μm filter and set aside; Dispersion: First weigh a certain amount of 3mm balls, toluene and n-butanol mixed solvent in a stirred mill, the ratio of toluene to n-butanol is 3:1-2:1, then add the pretreated second phase additive, nano alumina powder dispersant and additives in sequence, turn on the stirring switch and stir for 2 hours, the ratio of alumina is 90%-99%; Mixing: transfer the alumina and second phase additive slurry in the stirred mill to the drum ball mill, add a certain amount of PVB colloid according to the formula, run at a certain stirring rate for 24 hours, and transfer to the degassing tank through a 1μm filter; Vacuum degassing: The slurry in the drum ball mill is degassed with N 2 After the air pressure is sent into the degassing tank, the viscosity of the slurry and the corresponding ambient temperature are measured. The water bath temperature is set according to the viscosity and temperature of the slurry, and the appropriate degassing vacuum degree and time are set. After the slurry is effectively degassed, it is aged for a period of time for use; Molding and sintering: Set the scraper blade height to 0.3-0.6mm, the casting speed to 1-300mm / min, set the temperature and inlet and outlet air flux according to the environment, and adjust the casting speed and heating temperature appropriately according to the shrinkage of the drying area, so that the solvent volatilization on the surface and the back will not differ too much. The casting temperature and environment should also be strictly controlled to prevent the green body from delamination during the lamination process; After cutting, punching, printing, lamination and warm isostatic pressing for secondary molding, a block green body is obtained, and finally the binder is removed and sintered. The two-step sintering method is adopted. The sintering is vacuum sintering, hot pressing sintering under argon protective atmosphere or isostatic pressing sintering. The sintering temperature is 1500-1850°C, the sintering pressure is 20-50Mpa, and the temperature is kept for 1 hour, slowly cooled to 1500°C, kept for 2 hours, and then naturally cooled to room temperature to obtain high-performance nano-alumina ceramics.
2. A method for preparing fine-grained alumina ceramics according to claim 1, It is characterized in that The nano-alumina powder is nano-high-purity alumina powder, γ or α phase spherical particles, with a purity greater than or equal to 99.99%, a particle size D50=200nm, a ratio of D10 to D90 of 1:2 to 1:3, and a BET of 5 to 14 nm. 2 / g.
3. The method for preparing fine-grained alumina ceramics according to claim 1, It is characterized in that The second phase additive is Y 2 O 3 and MgO, where Y 2 O 3 , MgO particle size is 100nm~300nm, D10=30~50nm, D90=250~300nm, D90 / D10=4, Y 2 O 3 , MgO is 1:
2.
4. The method for preparing fine-grained alumina ceramics according to claim 1, It is characterized in that The solvent is any one of toluene, xylene, N-methylpyrrolidone, anhydrous ethanol, isopropanol, and n-butanol, or a mixture of two or more thereof, with a purity greater than or equal to 99.99% and a water content less than or equal to 0.05%.
5. The method for preparing fine-grained alumina ceramics according to claim 1, It is characterized in that The adhesive is PVB resin powder or polymethacrylic acid resin with a molecular weight of 30,000 to 130,000.
6. The method for preparing fine-grained alumina ceramics according to claim 1, It is characterized in that The plasticizer is dibutyl phthalate.
7. The method for preparing fine-grained alumina ceramics according to claim 1, It is characterized in that The dispersant is any one of KD-1, fish oil, lecithin, oleic acid amide and surfactant.
Citation Information
Patent Citations
Preparation method for non-water-based high-purity nanoscale aluminum oxide ceramics
CN104987050A
Fine-grained alumina ceramic, preparation method and application thereof
CN109400123A
High-purity high-strength aluminum oxide ceramic substrate and preparation method thereof
CN115849885A
Preparation method of aluminum oxide ceramic and aluminum oxide ceramic
CN117362011A
Method for fabricating multi-layer ceramics package
KR1020000058473A
Cited By
High-purity alumina electrostatic chuck hot isostatic pressing sintering method
CN119912242A
Preparation method of fine-grain alumina ceramic
CN120943614A
A method for preparing fine-grained alumina ceramics
CN120943614B
